Some Poncelet invariants for bicentric hexagons - Keady, Grant; McAndrew, A. (ATCM, 2024)
Tangential polygons are (convex) polygons for which every side is tangent to an inscribed circle. Cyclic polygons are those for which every vertex lies on a circle, the circumcircle. Bicentric $n$-gons are those which are both tangential and cyclic. Every triangle is bicentric. Bicentric quadrilaterals are those for which the sum of the lengths of opposite sides is the semiperimeter and for which opposite angles sum to $π$. Here we give some results pertaining to invariants of (convex) bicentric hexagons.